Hippocampal Deficits in Amyloid-β-Related Rodent Models of Alzheimer’s Disease - Vyas, Yukti; Montgomery, Johanna M.; Cheyne, Juliette E. (Frontiers in Neuroscience, 2020)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease that is the most common cause of dementia. Symptoms of AD include memory loss, disorientation, mood and behaviour changes, confusion, unfounded suspicions, and eventually, difficulty speaking, swallowing and walking. These symptoms are caused by neuronal degeneration and cell loss that begins in the hippocampus, and later in disease progression spreads to the rest of the brain. While there are some medications that alleviate initial symptoms, there are currently no treatments that stop disease progression. Hippocampal deficits in rodent models of AD have revealed synaptic, behavioural and circuit-level defects. These changes in synaptic function, plasticity, neuronal excitability, brain connectivity, and excitation/inhibition imbalance all have profound effects on circuit function, which in turn could exacerbate disease progression. However, a major limitation in this field is the lack of data and consensus to completely understand hippocampal deficits in AD. With the increasing development of in vivo recording techniques in awake and freely moving animals, future studies will extend our current knowledge of the mechanisms underpinning how hippocampal function is altered in AD, and aid in progression of treatment strategies that prevent and/or delay AD symptoms.